Polydatin attenuates chronic alcohol consumption-induced cardiomyopathy through a SIRT6-dependent mechanism. Issue 13 (21st June 2022) - Yu, Li-Ming; Dong, Xue; Li, Ning; Jiang, Hui; Zhao, Ji-Kai; Xu, Yin-Li; Xu, Deng-Yue; Xue, Xiao-Dong; Zhou, Zi-Jun; Huang, Yu-Ting; Zhao, Qiu-Sheng; Wang, Zhi-Shang; et al.
Abstract : Polydatin attenuates cardiac remodeling and mitochondrial dysfunction in an alcoholic cardiomyopathy model via SIRT6 signaling. Abstract : Polydatin has attracted much attention as a potential cardioprotective agent against ischemic heart disease and diabetic cardiomyopathy. However, the effect and mechanism of polydatin supplementation on alcoholic cardiomyopathy (ACM) are still unknown. This study aimed to determine the therapeutic effect of polydatin against ACM and to explore the molecular mechanisms with a focus on SIRT6–AMP-activated protein kinase (AMPK) signaling and mitochondrial function. The ACM model was established by feeding C57/BL6 mice with an ethanol Lieber–DeCarli diet for 12 weeks. The mice received polydatin (20 mg kg −1 ) or vehicle treatment. We showed that polydatin treatment not only improved cardiac function but also reduced myocardial fibrosis and dynamin-related protein 1 (Drp-1)-mediated mitochondrial fission, and enhanced PTEN-induced putative kinase 1 (PINK1)–Parkin-dependent mitophagy in alcohol-treated myocardium. Importantly, these beneficial effects were mimicked by SIRT6 overexpression but abolished by the infection of recombinant serotype 9 adeno-associated virus (AAV9) carrying SIRT6-specific small hairpin RNA. Mechanistically, alcohol consumption induced a gradual decrease in the myocardial SIRT6 level, while polydatin effectively activated SIRT6–AMPK signaling and modulated mitochondrial dynamics and mitophagy, thus reducing oxidative stress damage and preserving mitochondrial function. In summary, these data present new information regarding the therapeutic actions of polydatin, suggesting that the activation of SIRT6 signaling may represent a new approach for tackling ACM-related cardiac dysfunction.